Caracterização molecular de isolados de Trypanosoma cruzi provenientes de triatomíneos silvestres coletados no Estado do Espírito Santo, Brasil - Dario, Maria Augusta (2013)
Molecular studies have been used for characterization of the different Trypanosoma cruzi isolates, the etiologic agent of Chagas disease, wich comprises a complex population. In Espírito Santo state, Brazil, T. cruzi isolates were obtained from sylvatic triatomines, from June 2010 to May 2012 and DNA was extracted from 89 samples. The amplifications of the intergenic region of the calmodulin gene and TcSC5D gene were performed. The samples were sequenced and analyzed by Mega 5.05 software. Seventy eight samples were amplified by the intergenic region of the calmodulin gene, however, 66 samples were sequenced, indentifying TcII (19,7%), TcII-like (63,6%), TcIII (9,1%) and TcIV (7,6%) lineages. Sixty two samples were amplified and sequenced by the TcSC5D gene, identifying TcI (1,6%), TcII (82,2%), TcIII (8,1%) and TcIV (8,1%) lineages. In this study, was observed that the T. cruzi population circulating in triatomines species from ES is heterogeneous, predominating TcII and to a lesser extent TcI, TcIII and TcIV. It is not known, at the present, about the wild animals that act as reservoirs, where these populations circulate in the Atlantic rainforest, making difficult the correlation of these in this environment. Molecular characterization identified protozoan populations from the rainforest, but able to adapt to domiciliary transmission of Chagas disease.